Negative oxygen ion cathode composite material and preparation method and application thereof

Through negative oxygen ion cathode composite material and passive wall cloth technology, the high energy consumption and incomplete coverage of active negative oxygen ion generation technology is solved, and a high concentration and full coverage negative oxygen ion environment is achieved, and the reliability of the equipment is improved. and user experience.

CN119242096AActive Publication Date: 2025-01-03BEIJING TOPLI DECORATIVE MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411371061.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing active negative oxygen ion generation technology has problems such as high energy consumption, incomplete negative ion coverage, easy equipment damage, ozone and noise generation, and cannot achieve a full coverage healthy negative oxygen ion environment.

Method used

Using negative oxygen ion cathode composite material, the combination of nano tourmaline powder and specific ingredients and ultrasonic stirring technology can maximize the activation of nano tourmaline powder, improve the release capacity of negative oxygen ions, and uniformly distribute negative ions in the space through passive wall cloth to achieve Negative oxygen ion environment with high coverage area.

Benefits of technology

It significantly improves the negative ion concentration and coverage area in the space, reduces energy consumption, avoids equipment damage and noise, and provides a quiet and healthy high-negative oxygen ion environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067596120000031
    Figure BDA0005067596120000031
  • Figure BDA0005067596120000121
    Figure BDA0005067596120000121
  • Figure BDA0005067596120000131
    Figure BDA0005067596120000131
Patent Text Reader

Abstract

The invention provides a negative oxygen ion cathode composite material and a preparation method and application thereof. The negative oxygen ion cathode composite material disclosed by the invention is prepared from the following components in parts by weight: 45 to 55 parts of modified acrylic emulsion, 0.5 to 2 parts of a de-foaming agent, 1.5 to 2.5 parts of N, N-dimethyl-beta-hydroxyethyl octadecanamide gamma propyl quaternary ammonium nitrate, 25 to 35 parts of modified nano tourmaline powder and 15 to 25 parts of vinyl versatate. According to the negative oxygen ion cathode composite material disclosed by the invention, vinyl versatate and modified acrylic emulsion are used as low-temperature dispersion adhesion carriers, and meanwhile, the defoaming agent is compounded, so that the nano tourmaline can be activated and dispersed to the greatest extent, the negative oxygen ion release capability of the nano tourmaline is improved, and the negative ion concentration in a space is greatly improved; in addition, the N, N-dimethyl-beta-hydroxyethyl octadecanamide gamma propyl quaternary ammonium nitrate can enable the negative oxygen ions to be dispersed more uniformly and widely, so that the coverage area of the negative ions in the space is remarkably increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative oxygen ions, and in particular to a negative oxygen ion cathode composite material and a preparation method and application thereof. Background Art

[0002] The principle of the existing active negative oxygen ion generation technology is mainly to process the input DC or AC power through special treatment, and then upgrade it to AC high voltage through pulse circuits and high-voltage isolation lines, and then obtain pure DC negative high voltage after rectification and filtering through special grade electronic materials. The DC negative high voltage is connected to the release tip made of metal or carbon elements, and the DC high voltage at the tip is used to generate high corona, releasing a large number of electrons at high speed. These electrons cannot exist in the air for a long time and will be immediately captured by oxygen molecules in the air, thereby generating negative air ions.

[0003] Active negative oxygen ion generation technology is widely used. It can not only be used to improve indoor air quality, but also to improve the riding environment of vehicles such as cars. In addition, negative ion generators also have certain applications in the fields of medical care and health care. However, the application of active negative oxygen ion technology in indoor spaces has the following problems: 1) Negative ion generators consume a lot of electricity, resulting in energy consumption; 2) Negative ions exist in space for a very short time, and it is impossible to achieve full coverage of negative oxygen ions in the space by machines; 3) Negative ion generators are in a high-voltage discharge state for a long time, and the equipment is easily damaged, resulting in high maintenance costs in the later stage; 4) The operation of negative ion generators will produce ozone, which is not good for health; 5) Negative ion generators will cause noise and airflow disturbances, resulting in a poor experience.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a negative oxygen ion cathode composite material and its preparation method and application, which can activate and disperse nano-tourmaline to the greatest extent, improve the ability of nano-tourmaline to release negative oxygen ions, and greatly increase the negative ion concentration and coverage area in the space.

[0006] The negative oxygen ion cathode composite material of the invention comprises the following components in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-2 parts of defoamer, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano tourmaline powder and 15-25 parts of versatate vinyl carbonate.

[0007] Preferably, the negative oxygen ion cathode composite material of the present invention comprises the following components in parts by weight: 50 parts of modified acrylic emulsion, 1-2 parts of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate, 28-30 parts of modified nano-tourmaline powder and 17-20 parts of versatate.

[0008] Furthermore, the modified nano-tourmaline powder is composed of nano-tourmaline powder and borate, and the weight ratio of the nano-tourmaline powder to the borate is (3-5): (5-7); the particle size of the nano-tourmaline powder is 1000-3000 mesh, for example, 2000 mesh.

[0009] Nano-tourmaline is a borosilicate mineral with complex structure and composition, belonging to the trigonal crystal system. Since there are 5 polyhedrons in tourmaline, when the pressure or temperature acting on the crystal surface changes, the polyhedrons inside it will be distorted, among which the T polyhedron is the most distorted, so polarized charges appear on the two crystal end faces perpendicular to the c-axis, which is manifested macroscopically as a permanent electrostatic field around the tourmaline that is not affected by the external electric field.

[0010] When the pressure or temperature acting on the crystal surface changes, the external stress or thermal expansion of the crystal can polarize the unidirectional polar axis c-axis in the tourmaline crystal, and the charged particles in the crystal will be relatively displaced, and the positive and negative charge centers will shift along the c-axis, causing the total electrode moment of the crystal to change. The generated polarization charge is much larger than the spontaneous polarization effect, which makes the tourmaline have piezoelectric effect and pyroelectric effect, and has a strong far-infrared radiation function. At the same time, temperature and pressure changes will also cause the potential difference of the tourmaline crystal, ionizing the surrounding air, and the struck electrons will act on the nearby water and oxygen molecules and convert them into negative oxygen ions.

[0011] In addition, studies have shown that the ability of nano-tourmaline powder to release negative oxygen ions is closely related to its particle size and distribution; the present invention uses tert-butyl vinyl carbonate and modified acrylic emulsion as low-temperature dispersion and attachment carriers and compound defoaming agents, and stirring under constant temperature ultrasonic waves can activate and disperse the nano-tourmaline powder to the greatest extent, thereby improving the ability of nano-tourmaline to release negative oxygen ions and greatly improving the negative ion concentration in the space.

[0012] The molecular formula of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate is as follows:

[0013]

[0014] N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate can be evenly distributed in PVC and nano-tourmaline coatings. Its molecular structure and anionic properties enable it to eject negative oxygen ions into the air like a spring, making the dispersion of negative oxygen ions more uniform and extensive, significantly increasing the negative ion coverage area in the space. In addition, N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate and tert-butyl ester can improve the film-forming properties of wall cloth, making the appearance and quality of wall cloth better.

[0015] The present invention also provides a method for preparing the negative oxygen ion cathode composite material, comprising: mixing the components by weight, and then stirring evenly under ultrasonic conditions; wherein the stirring temperature is 30-40° C., and the stirring time is 20-40 min.

[0016] The present invention also provides a negative oxygen ion cathode composite slurry, comprising the following components in parts by weight: 10-20 parts of the above-mentioned negative oxygen ion cathode composite material and 80-90 parts of a printing medium; preferably, the printing medium is a water-based acrylic printing medium.

[0017] The present invention also provides a method for preparing the negative oxygen ion cathode composite slurry, comprising: mixing the components by weight and stirring evenly; preferably, the stirring speed is 1100-1300 r / min, and the stirring and mixing time is 5-15 min.

[0018] The present invention also provides the use of the negative oxygen ion cathode composite material or the negative oxygen ion cathode composite slurry in the preparation of passive negative oxygen ion wall coverings.

[0019] The present invention also provides a method for preparing a passive negative oxygen ion wall covering, comprising the following steps:

[0020] S1: evenly apply the negative oxygen ion cathode composite slurry onto the surface of the wall cloth;

[0021] S2: Drying and cooling the coated wall cloth to obtain a passive negative oxygen ion wall cloth.

[0022] In step S1, the coating amount of the negative oxygen ion cathode composite slurry is 20-25g / m 2 The preparation method of the wall cloth comprises: preparing a PVC film by using a wall cloth coating composition, hot-bonding the prepared PVC film onto a base cloth while it is hot, and cooling it by a cooling roller to obtain the wall cloth.

[0023] The wall cloth coating composition includes the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of dioctyl terephthalate (DOTP), 4-6 parts of epoxidized soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-30 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid.

[0024] Preferably, the wall cloth coating composition includes the following components in parts by weight: 100 parts of PVC resin, 30-32 parts of dioctyl terephthalate (DOTP), 4-5 parts of epoxidized soybean oil, 2-3 parts of composite calcium zinc stabilizer, 20-30 parts of stone powder, 28-30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.2-0.3 parts of stearic acid.

[0025] Furthermore, the composite calcium zinc stabilizer includes a calcium zinc stabilizer and a barium zinc stabilizer, and the mass ratio of the calcium zinc stabilizer to the barium zinc stabilizer in the composite calcium zinc stabilizer is 1:(1-2).

[0026] More specifically, the preparation of the wall covering comprises the following steps:

[0027] A) adding each component in the wall cloth coating composition by weight into a high-stirring mixing device and stirring and mixing to obtain a mixture;

[0028] B) conveying the mixed material to a mixing chamber for mixing, and conveying the mixed material to a twin-roll extruder for mixing to obtain a mixed material;

[0029] C) The mixed material is conveyed to a laminating machine for laminating, and the film formed by laminating is thermally attached to a base fabric, then cooled by a cooling roller, and then printed and embossed by a gravure printing machine to obtain a wall cloth.

[0030] In step A), the mixture is stirred and mixed at 40-50° C. for 4-6 minutes.

[0031] In step B), the mixture is kneaded at 130-140° C. for 5-10 min; the mixing time is 3-5 min.

[0032] In step C), the hot-sticking temperature is 165-185°C, preferably 170-180°C; the printing temperature is 100-120°C, and the embossing temperature is 185-205°C, preferably 200-205°C.

[0033] The above-mentioned wall cloth coating composition can improve the film-forming quality of the PVC film and the bonding effect between the PVC film and the base cloth, and the bonding firmness and durability are good, thereby improving the quality of the wall cloth; at the same time, in the process of preparing the PVC film, the PVC film is directly hot-bonded to the base cloth while it is hot, which can effectively avoid the generation of VOCs and static electricity during traditional cold glue bonding, and avoid the adverse effects of VOCs and static electricity such as consumption of negative oxygen ions and impact on product quality; in addition, the method of first normal printing and embossing and then processing the negative oxygen ion material can maximize the use of the characteristics of the negative oxygen ion material to excite negative oxygen ions, thereby improving the negative oxygen ion effect of the passive negative oxygen ion wall cloth.

[0034] In step S2, the vehicle speed (i.e., the linear speed of the printing roller) is set to 15-25 m / min, preferably 20-25 m / min, according to the depth of the wall cloth texture; the temperature is 100-150°C, preferably 130-150°C; the drying temperature is 100-120°C, and the drying time is 20-25s.

[0035] The present invention optimizes the composition of the negative oxygen ion cathode composite material and the preparation process of the passive negative oxygen ion wall cloth, uses different molecular materials, and utilizes the temperature difference and pressure difference in the air to form negative oxygen ions on the material surface, and realizes electron ejection through the cathode electrostatic molecular functional group, so that the negative oxygen ions can be distributed more widely in the space; at the same time, the practicality of the wall cloth that requires the whole house to be decorated is utilized, so as to realize the passive release of a large amount of negative oxygen ions in the whole space without using electrical energy or other chemical energy, so that the whole space realizes a high negative oxygen ion environment, which has both the harmony and beauty of the overall space and the healthy environment of high negative oxygen ions, is quiet, noiseless, and free of airflow disturbance, and has an excellent experience. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The raw materials used in each embodiment are as follows:

[0040] PVC resin: Type V suspension PVC resin, model S-1000, viscosity 1.87-1.89, water content 0.05-0.08%, purchased from Beijing Zhonghe Yongchang Economic and Trade Co., Ltd.;

[0041] Epoxidized soybean oil: model HM-01AD, purchased from Suzhou Easeo New Material Technology Co., Ltd.;

[0042] Stone powder: model CC-902, oil absorption value 35-38%, moisture 0.04-0.08%, purchased from Guangxi Hezhou Kelong Powder Co., Ltd.;

[0043] Environmentally friendly flame retardant: purchased from Liuyang Baolin Electrical New Materials Co., Ltd.;

[0044] Modified acrylic emulsion: model EMX-6A, solid content 21-24%, pH value 7.5, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.;

[0045] Nano tourmaline powder: particle size 2000 mesh, purchased from Beijing Senhai Oxygen Source Technology Co., Ltd.;

[0046] Defoaming agent: stearyl alcohol purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.

[0047] N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate: purchased from Polyli Chemical;

[0048] Water-based acrylic printing medium: model EMW, pH value 7.5-9.5, viscosity (No. 3 Zahn cup, 25° C.) 15-50 seconds, fineness better than 25 μm, purchased from Shanghai Dongxing Environmental Protection Ink Co., Ltd.

[0049] Example 1

[0050] The present embodiment provides a negative oxygen ion cathode material, comprising the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 30 parts of modified nano-tourmaline powder and 17 parts of versatate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0051] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 35° C. for 30 minutes to obtain a negative oxygen ion cathode material.

[0052] Example 2

[0053] The present embodiment provides a negative oxygen ion cathode material, comprising the following components in parts by weight: 50 parts of modified acrylic emulsion, 1.5 parts of defoaming agent, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 30 parts of modified nano-tourmaline powder and 18 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 3:7.

[0054] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 30° C. for 40 minutes to obtain a negative oxygen ion cathode material.

[0055] Example 3

[0056] The present embodiment provides a negative oxygen ion cathode material, comprising the following components in parts by weight: 50 parts of modified acrylic emulsion, 2 parts of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoyl γ-propyl quaternary ammonium nitrate, 28 parts of modified nano-tourmaline powder and 20 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 4:6.

[0057] The above components were mixed according to weight ratio and in the order of adding the liquid component first and then the powder component, and stirred in an ultrasonic constant temperature bath at 40° C. for 20 minutes to obtain a negative oxygen ion cathode material.

[0058] Example 4

[0059] This embodiment provides a method for preparing a passive negative oxygen ion wall covering, and the steps are as follows:

[0060] 1. Prepare the ingredients

[0061] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 32 parts of DOTP, 5 parts of epoxidized soybean oil, 2.5 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.3 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:1.

[0062] 2. Preparation of wall cloth printing and embossing semi-finished products

[0063] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 2 minutes, then add the other powder components, and mix at room temperature for 3 minutes to obtain a mixture.

[0064] The above mixture is conveyed to the mixing chamber, the temperature is set to 135℃, and the mixing is carried out for 8 minutes; after the mixing is completed, the mixture is further conveyed to the double-roll extruder for mixing for 4 minutes. After mixing, the material is quantitatively conveyed to the 4-roll film pressing machine for film pressing, and the film (i.e. PVC film) is hot-laminated on the cross cloth while hot, and the hot lamination temperature is 170℃, and then cooled by the cooling roller, and then the above semi-finished wall cloth is printed and embossed by a gravure printing machine with different patterns and colors. The printing temperature of each plate is controlled at 100℃, and the embossing temperature is controlled at 200℃ to obtain the printed and embossed semi-finished wall cloth.

[0065] 3. Preparation of passive negative oxygen ion wall covering

[0066] 20 parts of the negative oxygen ion cathode material prepared in Example 1 were mixed with 80 parts of an aqueous acrylic printing medium, and stirred at 1200 r / min for 10 min to prepare a negative oxygen ion cathode composite slurry.

[0067] The negative oxygen ion cathode composite slurry is evenly coated on the front of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, the vehicle speed was set to 20 m / min and the temperature to 130°C. It was dried at 110°C for 20 seconds, cooled, trimmed, and divided into 30 m / rolls according to standards to obtain passive negative oxygen ion wall cloth.

[0068] Example 5

[0069] This embodiment provides a method for preparing a passive negative oxygen ion wall covering, and the steps are as follows:

[0070] 1. Prepare the ingredients

[0071] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 30 parts of DOTP, 4 parts of epoxidized soybean oil, 2 parts of composite calcium-zinc stabilizer, 20 parts of stone powder, 28 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.2 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:2.

[0072] 2. Preparation of wall cloth printing and embossing semi-finished products

[0073] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 2 minutes, then add the other powder components, and mix at room temperature for 3 minutes to obtain a mixture.

[0074] The above mixture was transported to a mixing chamber, the temperature was set to 135°C, and the mixing was performed for 8 minutes; after the mixing was completed, the mixture was further transported to a twin-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively transported to a 4-roll laminating machine for laminating, and the film was hot-laminated onto the cross cloth while hot, the hot laminating temperature was 175°C, and then cooled by a cooling roller, and then the above semi-finished wall cloth was printed and embossed by a gravure printing machine with different patterns and colors, the printing temperature of each plate was controlled at 100°C, and the embossing temperature was controlled at 200°C, to obtain a printed and embossed semi-finished wall cloth.

[0075] 3. Preparation of passive negative oxygen ion wall covering

[0076] 15 parts of the negative oxygen ion cathode material prepared in Example 2 were mixed with 85 parts of an aqueous acrylic printing medium, and stirred at 1200 r / min for 10 min to prepare a negative oxygen ion cathode composite slurry.

[0077] The negative oxygen ion cathode composite slurry is evenly coated on the surface of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, set the vehicle speed to 25 m / min, the temperature to 140°C, dry at 100°C for 25s, cool and trim, and separate into 30 m / rolls according to standards to produce passive negative oxygen ion wall cloth.

[0078] Example 6

[0079] This embodiment provides a method for preparing a passive negative oxygen ion wall covering, and the steps are as follows:

[0080] 1. Prepare the ingredients

[0081] The wall cloth coating composition is prepared according to the following components in parts by weight: 100 parts of PVC resin, 30 parts of DOTP, 4 parts of epoxidized soybean oil, 3 parts of composite calcium-zinc stabilizer, 30 parts of stone powder, 30 parts of aluminum hydroxide, 5 parts of environmentally friendly flame retardant, 14 parts of titanium dioxide and 0.2 parts of stearic acid; wherein the composite calcium-zinc stabilizer is composed of a calcium-zinc stabilizer and a barium-zinc stabilizer, and the mass ratio of the calcium-zinc stabilizer to the barium-zinc stabilizer is 1:1.5.

[0082] 2. Preparation of wall cloth printing and embossing semi-finished products

[0083] Add the components of the wall cloth coating composition to a high-stirring mixing equipment according to their weight portions, and stir and mix at 45°C for 5 minutes; when adding the materials, add the PVC resin first, then add the liquid components, premix for 2 minutes, then add the other powder components, and mix at room temperature for 3 minutes to obtain a mixture.

[0084] The above mixture was conveyed to the mixing chamber, the temperature was set to 135℃, and the mixing was performed for 8 minutes; after the mixing was completed, the mixture was further conveyed to the double-roll extruder for mixing for 4 minutes. After mixing, the material was quantitatively conveyed to the 4-roll film press for film pressing, and the film was hot-laminated onto the cross cloth while hot, the hot lamination temperature was 180℃, and then cooled by the cooling roller, and then the above semi-finished wall cloth was printed and embossed by the gravure printing machine with different patterns and colors, and the printing temperature of each plate was controlled at 120℃, and the embossing temperature was controlled at 205℃, so as to obtain the printed and embossed semi-finished wall cloth.

[0085] 3. Preparation of passive negative oxygen ion wall covering

[0086] 10 parts of the negative oxygen ion cathode material prepared in Example 3 were mixed with 90 parts of an aqueous acrylic printing medium, and stirred at 1200 r / min for 10 min to prepare a negative oxygen ion cathode composite slurry.

[0087] The negative oxygen ion cathode composite slurry is evenly coated on the surface of the wall cloth printed embossed semi-finished product by squeezing using an upper silicone roller and a lower silicone roller with a hardness of 72 on a printing machine, and the coating amount is 20g / m 2 ; Then, according to the depth of the wall cloth texture, set the vehicle speed to 20 m / min, the temperature to 150°C, dry at 120°C for 20s, cool and trim, and separate into 30 m / rolls according to standards to produce passive negative oxygen ion wall cloth.

[0088] Comparative Example 1

[0089] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 4.

[0090] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate, 15 parts of nano-tourmaline powder (2000 mesh) and 17 parts of versatate.

[0091] Comparative Example 2

[0092] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 4.

[0093] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 50 parts of modified acrylic emulsion, 1 part of defoaming agent, 30 parts of modified nano-tourmaline powder and 19 parts of tert-butyl vinyl carbonate; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0094] Comparative Example 3

[0095] Except for the different composition of the negative oxygen ion cathode material, the rest is the same as Example 4.

[0096] The negative oxygen ion cathode material of this control example includes the following components in parts by weight: 67 parts of modified acrylic emulsion, 1 part of defoamer, 2 parts of N,N-dimethyl-β-hydroxyethyl octadecanoamide γ-propyl quaternary ammonium nitrate and 30 parts of modified nano-tourmaline powder; wherein the modified nano-tourmaline powder is composed of nano-tourmaline powder (2000 mesh) and sodium borate, and the weight ratio of nano-tourmaline powder to sodium borate is 1:1.

[0097] Comparative Example 4

[0098] The same as in Example 4 except that anionic polyacrylamide (APAM) was used to replace the N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate in Example 4.

[0099] Comparative Example 5

[0100] Except that negative oxygen ion material is used to replace the negative oxygen ion cathode material of Example 4, the rest is basically the same as Example 4 to obtain negative oxygen ion wall cloth.

[0101] The negative oxygen ion material composition of this control example is as follows: 20 parts of negative oxygen ion material (mineral powder produced in Lingshou County, purchased from the normal market) are mixed with 80 parts of water-based acrylic printing medium, and stirred at 1200r / min for 10 minutes to obtain negative oxygen ion slurry.

[0102] Test Example 1

[0103] The negative ion performance of the negative oxygen ion wall coverings of Examples 4-6 and Comparative Examples 1-5 was tested using the following method:

[0104] Negative ion concentration: using the material-induced air ion test method;

[0105] Negative ion free distance: Post 1 square meter of negative oxygen ion wall cloth, test the concentration of negative oxygen ions at different distances in a closed room, and the average value reaches 500ions / cm 3 The above position is the free distance of negative oxygen ions.

[0106] The results are shown in Table 1.

[0107] Table 1 Quality test results of each negative oxygen ion wall cloth

[0108]

[0109]

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative oxygen ion cathode composite material, characterized in that: The invention comprises the following components in parts by weight: 45-55 parts of modified acrylic emulsion, 0.5-2 parts of defoamer, 1.5-2.5 parts of N,N-dimethyl-β-hydroxyethyl octadecanoylamide γ-propyl quaternary ammonium nitrate, 25-35 parts of modified nano tourmaline powder and 15-25 parts of versatate vinyl carbonate.

2. The negative oxygen ion cathode composite material according to claim 1, characterized in that: The modified nano tourmaline powder is composed of nano tourmaline powder and borate, and the weight ratio of the nano tourmaline powder to the borate is (3-5): (5-7).

3. The method for preparing the negative oxygen ion cathode composite material according to any one of claims 1 to 2, characterized in that: include: The components are mixed according to weight, and then stirred evenly under ultrasonic conditions; Preferably, the stirring temperature is 30-40°C and the stirring time is 20-40 min.

4. A negative oxygen ion cathode composite slurry, characterized in that: The invention comprises the following components in parts by weight: 10-20 parts of the negative oxygen ion cathode composite material according to any one of claims 1-2 and 80-90 parts of a printing medium; preferably, the printing medium is a water-based acrylic printing medium.

5. The method for preparing the negative oxygen ion cathode composite slurry according to claim 4, characterized in that: include: Mix the components by weight and stir evenly; Preferably, the stirring speed is 1100-1300 r / min, and the stirring and mixing time is 5-15 min.

6. Use of the negative oxygen ion cathode composite material according to any one of claims 1-2 or the negative oxygen ion cathode composite slurry according to claim 4 in the preparation of passive negative oxygen ion wall coverings.

7. A method for preparing a passive negative oxygen ion wall cloth, characterized in that: The steps include: S1: uniformly coating the negative oxygen ion cathode composite slurry described in claim 4 on the surface of the wall cloth; S2: Drying and cooling the coated wall cloth to obtain a passive negative oxygen ion wall cloth.

8. The preparation method according to claim 7, characterized in that: The preparation method of the wall cloth comprises: preparing a PVC film by using a wall cloth coating composition, hot-bonding the prepared PVC film onto a base cloth while it is hot, and cooling it by a cooling roller to obtain the wall cloth.

9. The preparation method according to claim 8, characterized in that: The wall cloth coating composition includes the following components in parts by weight: 100 parts of PVC resin, 30-35 parts of DOTP, 4-6 parts of epoxidized soybean oil, 2-3 parts of composite calcium zinc stabilizer, 18-30 parts of stone powder, 28-32 parts of aluminum hydroxide, 4-6 parts of environmentally friendly flame retardant, 13-15 parts of titanium dioxide and 0.2-0.4 parts of stearic acid.

10. A passive negative oxygen ion wall covering, characterized in that: Prepared according to any one of the preparation methods of claims 7-9.

Citation Information

Patent Citations

  • Odor-free formaldehyde-free interior wall environmentally friendly coating and preparation method thereof

    CN106752555A

  • Imitated silk wallpaper or wall covering coating composition and imitated silk wallpaper or wall covering

    CN108589400A